Sixth-grade basic students ’acquisition of some of the values of citizenship and its relationship to their coping competence - Mohammed, Bassam Mahmoud; Slemon, Reem Mihoub; Ibrahim, Haifa Hassan (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the level of basic sixth-graders' acquisition of some of the values of citizenship and their level of competence in confrontation, and to reveal the relationship between the level of their acquisition of some values of citizenship and the level of competence of confrontation they have, and to reveal the differences between them in the acquisition of specific citizenship values (patriotism, commitment, responsibility The study sample consisted of (420) male and female students of the sixth grade, of whom (219) were pupils, and (201) pupils in the schools of Tartous city, and the study adopted the descriptive approach, and the Specific Citizenship Values Scale, and the Confrontation Efficiency Scale were used, which were prepared by the researcher using the previous studies. The city of Tartous, and their average level of confrontation competence, and the presence of a positive correlation between the scores of the study sample "of sixth grade students" in the scale of citizenship values and their scores in the scale of confrontation competence, a J The higher the level of students ’acquisition of citizenship values, the higher their level of coping competence, and there are statistically significant differences between the mean scores of the study sample of sixth-grade students on the scale of citizenship values according to the gender variable in favor of female students in the overall score and sub-dimensions. Except for the second dimension (commitment value), it was not statistically significant and there were no differences between males and females, and there were no statistically significant differences between the mean scores of the study sample of sixth grade students on the scale of coping efficiency according to the gender variable.
Keywords: citizenship; citizenship values; coping competence; sixth grade basic students